Bacterial and fungal microbiota in traditional Bangladeshi fermented milk products analysed by culture-dependent and culture-independent methods. (September 2018) - Nahidul-Islam, Sayed M.; Kuda, Takashi; Takahashi, Hajime; Kimura, Bon
Abstract: Dahi, chanar-misti, paneer, and borhani are traditional fermented milk products in Bangladesh. We evaluated the microbial properties of these products by analysing their bacterial and fungal microbiota using classical culture-dependent and culture-independent methods, including 16S rDNA (V4) and internal transcribed spacer (ITS) region pyrosequencing. The viable lactic acid bacteria (LAB) count was 6 and 8 log colony-forming units (CFU)/g. The yeast count was about 3 to 8 log CFU/g. The counts of aerobic gram-positive and gram-negative bacteria in paneer and borhani samples were similar to that of the LAB count. Pyrosequencing results revealed a high abundance of gram-negative bacteria ( Acinetobacter, Enterobacteriaceae, and Aeromonadaceae) in chanar-misti, and of Moraxellaceae in paneer. Various bacteria and fungi, including intestinal and mastitis-related microorganisms such as Bifidobacterium, Clostridium, Veillonella, and Clavispora lusitaniae, were found in chanar-misti . These results indicate that more safety processes are necessary for the preparation and manufacture of ready-to-eat (RTE) foods. Graphical abstract: Unlabelled Image Highlights: Dahi, chanar-misti, paneer, and borhani are traditional, fermented milk in Bangladesh. The microbiota was analysed by culture-dependent and –independent methods (MiSeq). Culture method showed high gram-negative rod counts in some samples. Contaminated samples showed high abundance of Acinetobacter and Pseudomonas . These results indicate that more safety processes are desired to use it for RTE foods.